A comprehensive review of carbon‐based and metal‐based electrocatalysts in the vanadium redox flow battery. Issue 2 (19th July 2021) - Taş, Mert; Elden, Gülsah
Abstract: The vanadium redox flow battery mainly consists of an electrode, membrane, and electrolyte. Positive and negative electrodes have great importance to the battery's performance. Electrodes were treated thermally, acid and plasma and modified with carbon‐based and metal‐based electrocatalysts to increase their electrochemical activity, active area, stability, and functional groups. In this study, comprehensive research was conducted on carbon‐based and metal‐based electrocatalysts. Furthermore, modification and treatment methods, charge‐discharge potential, maximum capacity, capacity fading, and energy efficiency of the electrode were examined at the same current density. The highest energy efficiency of the carbon‐based electrocatalyst was obtained for graphite felt doped with carbon nanoparticles. The energy efficiency of bare graphite felt was 67.4%, the efficiency increased up to 84.8% with the carbon nanoparticle electrocatalyst. Ohmic loss was reduced, and operating voltage window was enlarged. For metal electrocatalysts, the highest energy efficiency was obtained by titanium nitride modification. The energy efficiency increased from 68% to 89% in comparison to the bare electrode. Electrode kinetics and reversibility were improved by electrocatalyst doping, and the active area of the electrode was increased.